UWB Technology - Circuits and Systems 2020
DOI: 10.5772/intechopen.86071
|View full text |Cite
|
Sign up to set email alerts
|

Inner Tapered Tree-Shaped Ultra-Wideband Fractal Antenna with Polarization Diversity

Abstract: A coplanar waveguide (CPW)-fed third iteration inner tapered tree-shaped ultra-wideband (UWB) fractal antenna for polarization diversity applications is presented. The antenna comprises of two orthogonal fractal antenna structures to achieve polarization diversity performance across the frequency spectrum of 4.7-19.4 GHz. An isolation of more than 15 dB is accomplished. The designed antenna has a nearly omnidirectional radiation pattern with an average gain of 2.45 dB, very low values of envelope correlation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Patre and Singh [105] demonstrated the simulation and experimental studies on a novel compact and broadband CPW-fed flowershaped microstrip patch antenna. Singhal et al [106,107] presented a compact third-iteration inner-tapered tree-shaped fractal antenna for ultra-wideband applications and found that the bandwidth is enhanced by using CPW ground plane and increasing the number of iterations.…”
Section: Different Feeding Techniques Usedmentioning
confidence: 99%
“…Patre and Singh [105] demonstrated the simulation and experimental studies on a novel compact and broadband CPW-fed flowershaped microstrip patch antenna. Singhal et al [106,107] presented a compact third-iteration inner-tapered tree-shaped fractal antenna for ultra-wideband applications and found that the bandwidth is enhanced by using CPW ground plane and increasing the number of iterations.…”
Section: Different Feeding Techniques Usedmentioning
confidence: 99%